2023
DOI: 10.26508/lsa.202201607
|View full text |Cite
|
Sign up to set email alerts
|

Linear ubiquitination induces NEMO phase separation to activate NF-κB signaling

Abstract: The NF-κB essential modulator NEMO is the core regulatory component of the inhibitor of κB kinase complex, which is a critical checkpoint in canonical NF-κB signaling downstream of innate and adaptive immune receptors. In response to various stimuli, such as TNF or IL-1β, NEMO binds to linear or M1-linked ubiquitin chains generated by LUBAC, promoting its oligomerization and subsequent activation of the associated kinases. Here we show that M1-ubiquitin chains induce phase separation of NEMO and the formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 88 publications
(120 reference statements)
2
23
0
Order By: Relevance
“…Shortening or lengthening the linkers by the removal or addition of multiple residues on the Ub C-terminal tail reduced the ability of the polyUb hub to maximally promote phase separation of UBQLN2. This insight is important given that M1-linked polyUb chains are also best poised to promote multicomponent phase separation of other Ub-binding proteins such as NEMO and p62 (Du et al , 2022; Goel et al , 2023; Zaffagnini et al , 2018; Sun et al , 2018). These results suggest that the Ub code takes advantage of the optimal Ub-Ub spacing and the sensitivity of the high density (short spacer) side of the inclusion energy curve (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shortening or lengthening the linkers by the removal or addition of multiple residues on the Ub C-terminal tail reduced the ability of the polyUb hub to maximally promote phase separation of UBQLN2. This insight is important given that M1-linked polyUb chains are also best poised to promote multicomponent phase separation of other Ub-binding proteins such as NEMO and p62 (Du et al , 2022; Goel et al , 2023; Zaffagnini et al , 2018; Sun et al , 2018). These results suggest that the Ub code takes advantage of the optimal Ub-Ub spacing and the sensitivity of the high density (short spacer) side of the inclusion energy curve (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…K63-linked polyUb chains on cargo proteins interact with p62 to form pre-autophagosome condensates that later recruit autophagosome machinery (Zaffagnini et al, 2018;Sun et al, 2018); furthermore, autophagy cargo adaptor NBR1 condenses with K63-linked and M1-linked chains (Turco et al, 2021). NEMO condenses with K63-and M1-linked polyUb chains, but not K6-, K11-, K29-, K33-and K48-linked polyUb chains, to facilitate activation of the IKK complex leading to downstream NF-κB processing (Du et al, 2022;Goel et al, 2023). In contrast, hHR23B preferably binds to and condenses with K48-linked chains to form nuclear condensates and recruit the proteasome and other protein quality control components to degrade defective ribosomal proteins (Yasuda et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…[ 177 ] Met1‐/Lys63‐linked ubiquitination induces NF‐κB essential modulator (NEMO) compartmentalization to effectively activate NF‐κB signaling. [ 178 ] MAVS activation and aggregation are promoted by K63‐linked ubiquitination upon viral infection. [ 179 ] Therefore, DUBs are rationally involved in the regulation of PRRs signaling as summarized in Table 3 .…”
Section: The Roles Of Dubs In Immunitymentioning
confidence: 99%
“…Du et al (18) and Goel et al (19) have recently shown that ubiquitin can stimulate the LLPS transition of purified NEMO in vitro and that mutations that remove the C-terminal ubiquitinbinding domain of NEMO abolish this induced transition. Given our results above indicating that perturbation of the IVD interfered with the ability of NEMO to form higher order structures, we next determined whether IVD mutation affected LLPS of NEMO.…”
Section: An Inactivating Mutation Of Ivd Residues 145-153 Perturbs Ub...mentioning
confidence: 99%
“…For example, Shaffer et al showed that NEMO becomes more compact upon binding to IKKβ (13), and Hauenstein et al (12) and Catici et al (16,17) demonstrated that binding of linear ubiquitin leads to a variety of distinct conformational states of NEMO. Finally, two recent reports showed NEMO undergoes signal-induced liquid-liquid phase separation (LLPS) upon binding ubiquitin (18,19).…”
Section: Introductionmentioning
confidence: 99%